Cassava agronomy research and adoption of improved practices in China: Major achievements during the past 20 years - Li, Jun; Huang, Jie; Tian, Yinong; Zhang, Weite (International Center for Tropical Agriculture, 2001)
During the past 20 years, cassava agronomy research in China placed major emphasis on fertility maintenance, erosion control, planting methods, time of planting and harvesting, etc. Longterm fertilization trials conducted at GSCRI, CATAS and the Upland Crops Research Institute (UCRI) in Guangzhou, Guangdong, indicate that N was the most important nutrient for increasing cassava root yields during the early cropping cycles of cassava, but that K, and in some cases P, also became increasingly important. Results of soil erosion control trials conducted in Hainan and Guangxi showed that contour ridging, intercropping with peanut or the planting of vetiver grass contour hedgerows were the most effective practices for reducing soil erosion when cassava was grown on slopes. Planting cassava stakes vertically resulted in more rapid sprouting than horizontal or inclined planting, but there was not much difference in root yield among several methods of planting. Research on time of planting and harvesting cassava conducted at CATAS indicate that when cassava was harvested at 8 months after planting, highest yields were obtained when cassava was planted during the spring (Feb-May). However, when cassava was harvested at 12 months, time of planting had no consistent effect on yield. Effect of time of fertilizer application on cassava yield conducted at CATAS showed that a basal fertilizer application at 30 days after planting resulted in highest yields; there were no significant differences between a single application at 30 days and split applications at 30 and 60 days, or at 30, 60 and 90 days.